Theory and Practice of Action Semantics - Mosses, Peter D. (BRICS Report Series, 1996)
Action Semantics is a framework for the formal description of programming languages. Its main advantage over other frameworks is pragmatic: action-semantic descriptions (ASDs) scale up smoothly to realistic programming languages. This is due to the inherent extensibility and modifiability of ASDs, ensuring that extensions and changes to the described language require only proportionate changes in its description. (In denotational or operational semantics, adding an unforeseen construct to a language may require a reformulation of the entire description.) After sketching the background for the development of action semantics, we summarize the main ideas of the framework, and provide a simple illustrative example of an ASD. We identify which features of ASDs are crucial for good pragmatics. Then we explain the foundations of action semantics, and survey recent advances in its theory and practical applications. Finally, we assess the prospects for further development and use of action semantics. The action semantics framework was initially developed at the University of Aarhus by the present author, in collaboration with David Watt (University of Glasgow). Groups and individuals scattered around five continents have since contributed to its theory and practice.